Identification of Four-Jointed Box 1 (FJX1)-Specific Peptides for Immunotherapy of Nasopharyngeal Carcinoma - Chai, San Jiun (PLoS One, 2015)
Nasopharyngeal carcinoma (NPC) is highly prevalent in South East Asia and China. The poor outcome is due to late presentation, recurrence, distant metastasis and limited therapeutic options. For improved treatment outcome, immunotherapeutic approaches focusing on dendritic and autologous cytotoxic T-cell based therapies have been developed, but cost and infrastructure remain barriers for implementing these in low-resource settings. As our prior observations had found that four-jointed box 1 (FJX1), a tumor antigen, is overexpressed in NPCs, we investigated if short 9–20 amino acid sequence specific peptides matching to FJX1 requiring only intramuscular immunization to train host immune systems would be a better treatment option for this disease. Thus, we designed 8 FJX1-specific peptides and implemented an assay system to first, assess the binding of these peptides to HLA-A2 molecules on T2 cells. After, ELISPOT assays were used to determine the peptides immunogenicity and ability to induce potential cytotoxicity activity towards cancer cells. Also, T-cell proliferation assay was used to evaluate the potential of MHC class II peptides to stimulate the expansion of isolated T-cells. Our results demonstrate that these peptides are immunogenic and peptide stimulated T-cells were able to induce peptide-specific cytolytic activity specifically against FJX1-expressing cancer cells. In addition, we demonstrated that the MHC class II peptides were capable of inducing T-cell proliferation. Our results suggest that these peptides are capable of inducing specific cytotoxic cytokines secretion against FJX1-expressing cancer cells and serve as a potential vaccine-based therapy for NPC patients.